2018
DOI: 10.1111/jam.13745
|View full text |Cite
|
Sign up to set email alerts
|

Dermaseptin-S1 decreasesCandida albicansgrowth, biofilm formation and the expression of hyphal wall protein 1 and aspartic protease genes

Abstract: These data provide new insight into the efficacy of DS1 against C. albicans and its potential for use as an antifungal therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 43 publications
3
14
0
Order By: Relevance
“…It is noteworthy to mention here that engineered antifungal peptide histatin-5 altered the proteolysis activity of Sap2 and Sap9 and enhanced the antifungal activity ( Ikonomova et al, 2018 ). Similarly, dermaseptin-S1, another antimicrobial peptide, has been reported for its inhibitory effect on Saps ( sap1, sap2, sap3, sap9 , and sap10 ) along with growth, biofilm formation, morphological transition in C. albicans ( Belmadani et al, 2018 ). Further, morphological transition from yeast to hyphae is one of the important virulence factors of C. albicans.…”
Section: Discussionmentioning
confidence: 98%
“…It is noteworthy to mention here that engineered antifungal peptide histatin-5 altered the proteolysis activity of Sap2 and Sap9 and enhanced the antifungal activity ( Ikonomova et al, 2018 ). Similarly, dermaseptin-S1, another antimicrobial peptide, has been reported for its inhibitory effect on Saps ( sap1, sap2, sap3, sap9 , and sap10 ) along with growth, biofilm formation, morphological transition in C. albicans ( Belmadani et al, 2018 ). Further, morphological transition from yeast to hyphae is one of the important virulence factors of C. albicans.…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, previous studies have found leakage and morphological alterations in the artificial bacterial membrane after treatment with fluorescent-labelled dermaseptins [ 21 , 22 ]. More recently, using the electron microscopy, a dermaseptin peptide, DS1, was found to distort the cell wall surface, proposing that the cytolysis or cell membrane disruption of C. albicans eventually cause cell death [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Each exposure condition (CCS, NF, NR, and Ctrl) was performed in a separate exposure chamber to avoid culture cross-contamination. At the end of each exposure regime (2 or 3 days), C. albicans growth was determined by MTT assay, as previously reported [15]. Results were reported as means ± SD, n = 5.…”
Section: Methodsmentioning
confidence: 99%
“…Following each exposure, cultures were incubated for 60 min before the culture medium was refreshed. Following the second exposure, C. albicans cultures were incubated for 16 h at 37 °C and subsequently used to extract total RNA, as we previously reported [15]. The RNA (1 μg of each sample) was reverse transcribed into cDNA by means of the iScript cDNA Synthesis kit (Bio-Rad) and used for quantitative PCR (qPCR).…”
Section: Methodsmentioning
confidence: 99%